2011
DOI: 10.1111/j.1095-8649.2010.02895.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal influences on thiamine status of walleye Sander vitreus ova

Abstract: Concentrations of the various forms of thiamine (vitamin B(1) ) were determined in walleye Sander vitreus ova from three central North American lakes. Total thiamine concentrations in ova from Lake Winnipeg S. vitreus were approximately three times greater (mean 12 nmol g(-1) ) than in those from Lakes Erie or Ontario. The percentage of thiamine in the active form (thiamine pyrophosphate, TPP) was highest in Lake Ontario ova (mean 88%) and lowest in those from Lake Winnipeg (mean 70%). Neither ova total thiami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Several Lake Superior fish had more enriched carbon isotope levels, and these were associated with lower egg thiamine concentrations. The observation that egg thiamine levels in lake whitefish may be related to maternal diet is in concordance with observations on lake trout and walleye (Wiegand et al, 2011) from the Great Lakes. We observed no significant relationship between isotopic nitrogen signatures and thiamine levels in lake whitefish eggs across the three lakes.…”
Section: Discussionsupporting
confidence: 79%
“…Several Lake Superior fish had more enriched carbon isotope levels, and these were associated with lower egg thiamine concentrations. The observation that egg thiamine levels in lake whitefish may be related to maternal diet is in concordance with observations on lake trout and walleye (Wiegand et al, 2011) from the Great Lakes. We observed no significant relationship between isotopic nitrogen signatures and thiamine levels in lake whitefish eggs across the three lakes.…”
Section: Discussionsupporting
confidence: 79%
“…Thiaminase, commonly found in fish meat, produces severe thiamine deficiency in wild stocks (Honeyfield et al, 2005). It leads to a decline in the overall egg thiamine content (Wiegand et al, 2011) which eventually causes early mortality syndrome and increased mortalities in fish larvae (Keinanen et al, 2012). They have demonstrated that thiamine injection has positive effects on reproductive performance in the sturgeon Acipenser ruthenus, and the negative impacts of anti-thiamine in the offspring can be reduced by the injection of this vitamin into the broodstock.…”
Section: Discussionmentioning
confidence: 99%